Analisa Kerusakan Jalan terhadap Ruas Jalan di Jalan Raya Turi, Lamongan, Jawa Timur - Rozaq, Ainur; Hartantyo, Sugeng Dwi; Romadhon, Romadhon (Jurnal Talenta Sipil, 2026)
Roads are important infrastructure that supports smooth transportation and economic growth. This research aims to analyze the pavement condition on Jalan Raya Turi - Kemlagi Gede, Turi District, Lamongan Regency, East Java, using the Pavement Condition Index (PCI) method. This research was conducted along 550 meters of road divided into six observation segments. The PCI method was chosen because it is able to evaluate road conditions based on the type of damage, severity, and extent of damage in each survey unit. The results showed that the highest PCI value was 82 and the lowest was 59, with an average value of 70.00. Based on the PCI classification, the general pavement condition falls into the good to very good category. The damage found can still be handled with routine and light maintenance without requiring heavy structural repairs.